Evaluation of the Therapeutic Effectiveness of Polymyxin B Versus Colistin in Carbapenem-resistanct Klebsiella pneumoniae-Associated Bacteremia - Hasan, Md Jahidul; Rabbani, Raihan; Bachar, Sitesh C (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Polymyxins are the last resort antibiotics for treating carbapenem-resistance Klebsiella pneumoniae (CR-Kp)-associated bacteremia. The main aim of this study was to demonstrate the therapeutic effectiveness of polymyxin B versus colistin in the treatment of CR-Kp-associated Bacteremia. This 12-month long cross-sectional study was conducted on 54 and 47 patients suffering from CR-Kp-associated Bacteremia, and residing into two separate groups, they were treated with polymyxin B and colistin, respectively. After 5 day-treatment, the microbiological eradication rate was found 96.30% (52; n=54) in polymyxin B group and 87.23% (41; n=47) in colistin group. In the 30-day mortality rate-comparison, 51.03% more death was found in colistin group (34.04 %, n= 47) than the polymyxin B group (16.67 %, n= 54). In this study, Polymyxin B showed superior therapeutic potentiality with less number of secondary infections and 30-day mortality rate in CR-Kp-associated bacteremia than colistin. Dhaka Univ. J. Pharm. Sci. 18(2): 209-215, 2019 (December)